2009
DOI: 10.3855/jidc.122
|View full text |Cite
|
Sign up to set email alerts
|

The role of unpasteurized hawked milk in the transmission of brucellosis in Eldoret municipality, Kenya

Abstract: Background: Brucellosis is a zoonotic disease that continues to infect many people worldwide. Though its mortality rate is low, long convalescent periods associated with brucellosis translate into reduced socio-economic capacity of the people affected. Human brucellosis is mostly transmitted from animals. In Kenya, the prevalence of the disease has increased recently, along with the increased hawking of unpasteurized milk. The extent of the risk such raw milk poses to human health with respect to brucellosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The present study determined risk factors for human brucellosis among occupationally linked household members in Borena pastoral region. Studies in Kenya by Namanda et al [63] and in Tanzania by John et al [64] have reported occupation as a risk factor for acquiring brucellosis, whereby animal handlers and associated professionals were the most susceptible groups. In our study, it was revealed that 98.8% of participants had no knowledge of brucellosis.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study determined risk factors for human brucellosis among occupationally linked household members in Borena pastoral region. Studies in Kenya by Namanda et al [63] and in Tanzania by John et al [64] have reported occupation as a risk factor for acquiring brucellosis, whereby animal handlers and associated professionals were the most susceptible groups. In our study, it was revealed that 98.8% of participants had no knowledge of brucellosis.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Consumption of unpasteurized milk was reported to be a risk factor for acquiring brucellosis in human [63,65,66]. Practices of consuming raw milk among Borena pastoral communities is due to a belief that boiling a milk would reduce its nutritional content.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%